Safety of a proposed amendment of the specifications for steviol glycosides (E 960) as a food additive: to expand the list of steviol glycosides to all those identified in the leaves of Stevia Rebaudiana Bertoni - Younes, Maged (John Wiley and Sons Inc., 2020)

(untitled) (EFSA J)
The EFSA Panel on Food Additives and Flavourings (FAF) provides a scientific opinion on the safety of the proposed amendment of the specifications for steviol glycosides (E 960) as a food additive, in particular to expand the list of steviol glycosides to 60 steviol glycosides identified in the leaves of Stevia Rebaudiana Bertoni. With the existing specifications, the food additive must be comprised of not less than 95% of the 11 named steviol glycosides. The proposed change is to include all 60 steviol glycosides in the same limit value of 95% and this would allow the presence of up to 5% of impurities. FAF Panel considered that all steviol glycosides share the same metabolic fate, and therefore, the safety of 60 identified steviol glycosides can be based on read‐across from toxicological data previously evaluated by EFSA and the acceptable daily intake (ADI) of 4 mg/kg body weight (bw) per day will apply to all those steviol glycosides. However, according to the proposed change in specifications, there remains a small but not insignificant fraction of the additive that would be undefined and therefore cannot be evaluated by the Panel. The Panel concluded that the inclusion of the 60 steviol glycosides in the proposed specifications for steviol glycoside (E960) would not be of safety concern. However, the Panel cannot conclude on the safety of the proposed amendment to the specifications of steviol glycosides (E 960) as food additive if the purity assay value of not less than 95% for the total content of steviol glycosides is maintained.